Governing child care in neoliberal times: Discursive constructions of children as economic units and early childhood educators as investment brokers. Issue 3 (September 2015) - Gibson, Megan; McArdle, Felicity; Hatcher, Caroline
At any given time in the field of early childhood, there are discourses at play, producing images of children, and these ways of seeing children might be competing, colliding and/or complementing each other. It is fairly widely accepted that in many countries there are versions of dominant discourses that shape and are shaped by current practices in the field of early childhood. These include (1) romantic notions of children running free and connecting with nature and (2) the 'Bart Simpson' version of the naughty, cute or savage child, untamed and in need of civilising. These are far from being the only two discursive constructions of children present in current policies and practices. If early childhood professionals are to be active in shaping and implementing policies that affect their work and workforce, it is important that they are aware of the forces at play. In this article, we point to another powerful discourse at play in the Australian context of early childhood education, the image of children as economic units: investments in the future. We show how a 'moment of arising' in contemporary policy contexts, dominated by neoliberal principles of reform and competition, has charged early childhood educators in Australia with the duties of a 'broker', ensuring that young children are worth the investment. In this article, we begin with (1) a key policy document in early childhood education in Australia and examine the discursive affordances which shape the document. Next, (2) we pinpoint the shifts in how the work of child care is perceived by interrogating this key policy document through a methodology of discursive analysis. We then turn attention (3) to the work of this policy document along with other discourses which directly affect images of children and the shaping role these have on the work of educators. We conclude with (4) a consideration of how the work of early childhood professionals has come to be shaped by this economic discourse, and how they are being required to both work within the policy imperatives and likely to resist this new demand of them.